Projeções de Pecipitação dos Modelos do Cmip5 para o Cenário rcp8.5 Sobre o Nordeste Brasileiro - Guimarães, Sullyandro Oliveira; Costa, Alexandre Araújo; Sales, Domingo Cassain; Vasconcelos Júnior, Francisco das Chagas (Ciência e Natura, 2013)
Precipitation is one important variable highlighted over the Brazilian Northeast (NEB), to assessment of water resources, extreme events, and etc. In this sense the analysis is made of the precipitation modeled for the present climate (1985-2005), and future climate (2079-2099) projected in a scenario of high emissions of greenhouse gases.